A Rare Case of Benign Intracranial Hypertension with Bilateral Complete Visual Loss and Sixth Nerve Paresis - Chandana Chakraborti; Nabanita Barua; Sheuli Kumar; Rosy Chishti (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Introduction: Benign intracranial hypertension (BIH) is a disorder defined by symptoms and signs suggestive of increased intracranial pressure (ICP) in the absence of any cause evident on neuroimaging or other evaluations. Usually the disease has a variable outcome but chances of severe visual loss are only 6%. Methods: We report a case of 50 year old lady who presented to us with severe headache. Visual acuity was 20/20 both eyes. Anterior segment was within normal limit. Post segment evaluation revealed bilateral disc oedema. Thorough radiological and neurological examination confirmed diagnosis of Benign intracranial hypertension (BIH). We advised medical treatment and referred the patient to Neurology OPD for further management. She was lost to follow up to us for 4 months. She discontinued medicines in between. Her vision was 20/200 and fundus showed atrophic disc edema. We restarted previous medicines and referred to Neurology where she was admitted and managed conservatively. Finally she presented after 2 months with no perception of light both eyes. Examination revealed bilateral afferent pupillary defect and sixth nerve paresis. Fundus showed bilateral disc pallor. Conclusion: Our endeavor is to document that BIH is not always benign condition. A multidisciplinary approach should be taken to look for early progression and appropriate intervention.